EDUCATIONAL VALUES FROM THE CHARACTERS OF EL SHIRAZY'S NOVEL 'AYAT-AYAT CINTA': A SOCIOLOGY OF LITERATURE PERSPECTIVE - Ana Rosmiati (Leksema: Jurnal Bahasa dan Sastra, 2022)
This article aimed at finding out the educational values reflected by characters in the novel Ayat-ayat Cinta written by Habiburrahman El Shirazy from sociological approach to literature. This was a descriptive-qualitative research with textual data in the form of words, phrases, clauses, sentences, and discourse uttered by the characters and narrated by the author in the novel. The result shows that the novel contains some moral messages as well as educational values. Each character in this novel carries educational messages through their characterizations and plot of the story.